BIM-Based Time and Cost Tracking of Construction Projects Taking Quality Management into Consideration - Abdulaziz, Ramy Adel; Sobhy, Ehab Shehata; El-Yamany , Magdy Abdel Aziz (International Journal of Membrane Science and Technology, 2023)
: The construction industry has long suffered from the lack of time and cost tracking systems that take the impact of quality issues into account. Accordingly, emphasizing the integration of Earned Value Management (EVM) and Building Information Modeling (BIM) taking quality management into consideration has become a crucial requirement. The main objectives of this study are to address quality management into BIM and enhance monitoring of project's time and cost performance via addressing the effect of quality issues in order to support making the proper decisions to restore the original plan's progress. Using the capabilities of Application Programming Interface (API) and C# as a powerful programming language, this enhancement is achieved by the development of a BIM-based model including three plugins: Bill of Quantity (BOQ) estimator, Quality inspector, and EVM controller. BOQ estimator tool includes data about element's ID, the corresponding category, geometric properties and the corresponding cost details. Quality inspector tool includes, for project activities as well as elements making up each activity, the related most recent quality status from on-site records. On the other hand, EVM Calculator tool represents the core of the mathematical model that includes planned/budgeted data, actual data and results of EVM analysis providing performance indices and cost/time variances. In this paper, authors focus on providing details about the mathematical model developed to implement EVM Calculator tool via combining the effect of task's quality status on EVM variables. The proposed mathematical approach is validated using four different simulation scenarios. Results of the proposed model were compared with those obtained (and then revised to reflect the effect of quality status on task's/project's time and cost) using primavera P6. The results on comparison show the efficiency of the developed model providing an opportunity to address the effect of quality issues into EVM analysis that would reduce calculation time and eliminate chances of human errors associated with altering of results.